A study to assess knowledge and skill among doctors about hand hygiene, WHO five moments, personal protective equipment’s and assess the impact of educational intervention, in tertiary care hospital, Al Qassim provenance of Saudi Arabia - Kumar Gupta, Sanjay; Al Khaleefah, Fahd Khaleefah; Saifi Al Harbi, Ibrahim; Jabar, Sinimol; Torre, Marilou A.; Mathias, Sunitha Lorin (International Journal Of Community Medicine And Public Health, 2018)
Background: Hand hygiene (HH) is now to be considered as one of the most important effective measure of infection control activities. This is because enough scientific evidence suggested the observation that if properly implemented, hand hygiene alone can significantly reduce the risk of cross-transmission of infection in healthcare facilities. Methods: Hospital based educational intervention. Results: The study results showed the overall improvement pre and post educational intervention regarding hand hygiene skills, five moments and donning and doffing of PPE was significantly improved from 56.50% to 94.51%. If we see the knowledge and skills among doctors between department than we found significantly low knowledge and skills among (pre-interventional) doctors of radiology 23.33% followed by orthopedics 42.50%. The post educational interventions improvement in intensive care unit, laboratory, ENT and dental department were near 100% and lowest observed in departments in pediatrics (84%). Conclusions: The study shows that need for the doctors to increase their knowledge and skill related to infection prevention and control practice by assessing their existing knowledge and skills in small groups and according to observations intervention also plan and its improved knowledge and skill significantly.